2000
DOI: 10.1038/sj.ejcn.1600917
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake of working women in Bangkok, Thailand, as studied by total food duplicate method

Abstract: Objectives: To establish a general view of food habits in Thailand, and to make a quantitative assessment of rice dependency of Thai people. Design: Cross-sectional study. Setting: Community. Subjects: 52 non-smoking and non-habitually drinking adult women in Bangkok participated in the study. Methods: The participants offered 24 h food duplicates and peripheral blood samples, and underwent clinical examination including anthropometry. The duplicates were subjected to nutritional evaluation taking advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Matsuda-Inoguchi et al [36] investigated the nutrient intakes of working women in Bangkok by the total food duplicate method and reported that although about half of the women had insufficient energy intakes, lipid intakes such as vegetable oil, butter, and lard were in excess in more than half of the women. Yoshimoto et al [37] studied the association between socioeconomic changes and health status among 140 middle-aged subjects residing in an urban area of Chiang Mai province and reported that women had significantly higher values of body fat percent and HDL cholesterol and that men had significantly higher values of triglyceride and arteriosclerosis index.…”
Section: Discussionmentioning
confidence: 98%
“…Matsuda-Inoguchi et al [36] investigated the nutrient intakes of working women in Bangkok by the total food duplicate method and reported that although about half of the women had insufficient energy intakes, lipid intakes such as vegetable oil, butter, and lard were in excess in more than half of the women. Yoshimoto et al [37] studied the association between socioeconomic changes and health status among 140 middle-aged subjects residing in an urban area of Chiang Mai province and reported that women had significantly higher values of body fat percent and HDL cholesterol and that men had significantly higher values of triglyceride and arteriosclerosis index.…”
Section: Discussionmentioning
confidence: 98%
“…Investigators have reported mean Ca intakes of pre-menopausal adult women in Asian countries, such as Taiwan, Korea, and Thailand, to be 392-648 mg/day Shimbo et al 1997;Matsuda-Inoguchi et al 2000). However, there have been a relatively few reports on Ca intake in young Asian women.…”
Section: Discussionmentioning
confidence: 99%
“…Total dietary intakes for adult reference groups were reporteds for Br and I in the UK, 316 Cd and Si in Belgium, 125,317 Cd and Pb in south-east Asia and Japan, 127,318 I and Sr in Germany, 319,320 Mn in India 321 and for eight elements measured in foods in Thailand. 322 Again using duplicate diet analysis, the intake of Cd by women in Japan was found to have fallen by 32% between 1981 and 1997 although it is still high compared with other countries. 129 Rice was seen to be the major source of the Cd.…”
Section: Dietary Intake Studiesmentioning
confidence: 99%